Anna Bayerová, Anna Fischer-Dücklemann: Physicians, Health and Sexuality in the 19th and 20th Century (Theatrum historiae, 2013)
The study will compare the life and work of two women who belonged to the first generation of female physicians in Central Europe, Anna Fischer-Dückelmann and Anna Bayerová. At the turn of the 19th and 20th century both of them treated especially children and women – towards women they mediated in an intelligible form their knowledge, teach them to be familiar with their own bodies, souls and abilities. Fischer-Dückelmann was born in Austria, Bayer in Bohemian lands. They had a lot in common - they were almost the same age, both received their diplomas in Switzerland, Fischer in Zurich, where women could study at the medical faculty since the year 1864, Bayerová received her diploma in Bern. Both have contributed significantly to the popularization of medicine, and both of them were avowed by the feminist movement. Anna Fischer is considered as representative of “maternal feminism”. In some ways, however, they differed: Anna Fischer finished her study of medicine as a married woman (with material and psychological support of her husband), and the circumstances allowed her quite freely perform her profession, Anna Bayerová had to enforce everything and was never fully accepted as a doctor in the milieu of Bohemian lands.
Keywords: Anna Bayerová; Anna Fischer-Dückelmann; physician; history of medicine; gender history